Computer simulation of water effluent propagation in the reservoirs systems - Kurakbayeva, Sevara Dzhumagaliyevna; Umarova, Zhanat Rysbayevna; Kalbayeva, Aizhan Tazhiklhanovna; Kurakbayev, Dzhumagali Salbekovich; Akhmetova, Sabira Tastanovna; Musabekov, Akhmetbek Akhylbekovich (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The task of the research was to build and analyze a model of the dynamics of pollution of a flowing reservoir and systems of communicating reservoirs with and without taking into account water filtration in the soil as a result of external sources (effluents from industrial enterprises). This work was aimed at studying the change in temporal dynamics, taking into account the concentration of impurities in the volumes of three reservoirs during the periods of discharge and completion, lasting 30 days. Numerical experiments were carried out for various flow rates and compositions of filtration coefficients to study the relaxation times of pollution in the system of reservoirs. Also, software was developed that analyzes the change in the concentration of impurities in the system of reservoirs. As a result, it was found that the pollution pattern is more dependent on the topology of the watercourse network.